2000
DOI: 10.1038/sj.onc.1203959
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Bax to mitochondria induces apoptotic cell death in Indole-3-carbinol (I3C) treated breast cancer cells

Abstract: Epidemiological studies have suggested that the consumption of fruits and vegetables that provide several classes of compounds, including Indole-3-carbinol (I3C), may have chemopreventive activity against breast cancer. Several in vitro and in vivo animal studies also provide convincing evidence for the anti-tumor activity of I3C, however, the molecular mechanism(s) by which I3C exerts its biological e ects on breast cancer cells has not been fully elucidated. In this study, we investigated the e ects of I3C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…MiR-125a-prec recognizes as a main target the Erbb2 oncogene, which plays a fundamental role in breast cancer (40) and is also expressed in lung carcinomas (41). I3C exerts antiproliferative and apoptotic effects in breast cancer cells expressing Erbb2 (42). It is noteworthy that I3C was the only chemopreventive agent that had some effect on the ECS-related overexpression of miR-294 , which is involved in gene transcription and recognizes transcriptional repressor genes (e.g., zinc finger protein 697; AT-rich interactive domain 4A) as main targets.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-125a-prec recognizes as a main target the Erbb2 oncogene, which plays a fundamental role in breast cancer (40) and is also expressed in lung carcinomas (41). I3C exerts antiproliferative and apoptotic effects in breast cancer cells expressing Erbb2 (42). It is noteworthy that I3C was the only chemopreventive agent that had some effect on the ECS-related overexpression of miR-294 , which is involved in gene transcription and recognizes transcriptional repressor genes (e.g., zinc finger protein 697; AT-rich interactive domain 4A) as main targets.…”
Section: Discussionmentioning
confidence: 99%
“…As a mechanism of apoptosis induction, I3C has been to shown to down-regulate anti-apoptotic gene products (Bcl-2, Bcl-X L , survivin, inhibitor-of-apoptosis protein; IAP, X chromosome-linked IAP; XIAP, Fas-associated death domain protein-like interleukin-1-beta-converting enzyme inhibitory protein; FLIP), up-regulate pro-apoptotic factors (such as Bax), release mitochondrial cytochrome C as well as activate caspase-9 and caspase-3 [26-37]. In human cancer cell models, indoles (I3C/DIM) have been shown to induce apoptosis in breast [27,28,30-34,38-42], squamous cell carcinoma [43], cholangiocarcinoma [44], colon [45-49], cervical [37,50], ovarian [51], pancreatic [52,53] and prostate [29,54-57] cancer cells.…”
Section: Induction Of Cell Death By Indolesmentioning
confidence: 99%
“…Our own investigations with apoptosis-induction by indoles, with focus on modulation of pro-Vs. anti-apoptotic factors have revealed that indoles can inhibit Bcl-2 and Bcl-X L protein expression in prostate and breast cancer cells [30,31]. The ratio of Bax to Bcl-2 was significantly increased after just 24 hours of treatment which corresponded with a jump in the number of apoptotic cells.…”
Section: Induction Of Cell Death By Indolesmentioning
confidence: 99%
See 2 more Smart Citations